The Impact of ESG Investments on Labor Productivity: Mechanisms and Long-Term Effects - Petkova, Anika (Research Papers, 2025)
ESG investments, as an essential component of sustainable finance, exert both direct and indirect effects on labor productivity. This influence materializes through the adoption of energy-efficient technologies and the optimization of resource use, which generate economies of scale and enhance total factor productivity. The social dimensions of ESG investing—improved working conditions, professional training, and a safe work environment—strengthen employee motivation and contribute to higher labor efficiency. Digitalization, automation, and the application of artificial intelligence further amplify the positive impact of sustainable investments. Owing to these advantages, ESG investing is increasing recognized as a key mechanism for improving labor productivity and fostering long-term sustainable economic growth.